Impact of Unbalanced Diet on Mesenteric Anatomy and Gastrointestinal Disorders in the Pakistani Population. A Clinical Study - Irum Naz, Wajeeha Ansar, Muhammad Faisal Khan, Sabahat Zulfiqar, Mushtaq Ahmad, Muhammad Umar, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Pakistan has been rapidly urbanized, and this has resulted in a change from traditional, nutrient-rich meals to energy, nutrient-poor diets. They are associated with increased incidences of metabolic and GI disorders. Unbalanced diets may have adverse affects on an active organ, the mesentery, which plays a role in lipid metabolism and immune regulation. Objectives: The objective of this clinical study was to analyze the association of unbalanced dietary patterns with mesenteric anatomical anomalies and the severity of GI symptoms in a Pakistani population. Methodology: Present study was conducted in tertiary care hospitals of Nawaz Sharif Medical College, Gujrat and Khawaja Muhammad Safdar Medical College Sialkot from January 2022 to January 2023. One 100 adult patient (18 to 65 years) presenting with GI symptoms at tertiary care centers were enrolled in a 12-month prospective observational study. A validated food frequency questionnaire (FFQ) specific to local dietary habits was used to assess dietary intakes, and participants were categorized into balanced and unbalanced diet groups. These included comprehensive clinical evaluations, including anthropometric measurements and standardized GI symptom assessments. Mesenteric fat thickness, arterial wall thickness, and vessel compliance were evaluated by radiological means using abdominal ultrasonography and computed tomography (CT) scans. Associations between dietary quality, mesenteric parameters, and GI symptom severity were assessed through statistical analyses using Pearson’s correlation and multivariate regression (SPSS version 26). Results: Among patients with unbalanced diets, the BMI and GI symptom severity were significantly higher. Increased mesenteric fat thickness and arterial wall thickness and reduced vessel compliance (p < 0.001) were the radiological findings. Pearson’s correlations were significant (p < 0.001) between poor dietary quality and mesenteric fat (r = 0.48) and between mesenteric fat and GI symptoms (r = 0.41). Unbalanced diet score (β = 0.35, p = 0.002) and mesenteric fat thickness (β = 0.32, p = 0.004) were independent predictors of GI symptom severity by multivariate regression. Conclusion: Adverse mesenteric changes and increased GI symptom severity in the Pakistani population are highly associated with unbalanced diets. Keywords: Unbalanced Diet, Mesenteric Anatomy, Gastrointestinal Disorders, Pakistani Population, Nutritional Assessment, Clinical Study